Vascular Graft Infection: Detection by 123I-Labeled Antigranulocyte Antibody (Anti-NCA95) Scintigraphy - Cordes, M.; Hepp, W.; Langer, Ruth; Pannhorst, J.; Hierholzer, J.; Felix, R. (Nuklearmedizin - NuclearMedicine, 1991)
A total of 40 scintigraphic examinations were performed after vascular reconstructive surgery in 27 patients in whom there was a clinical suspicion of vascular graft infection. Whole-body gamma camera images were obtained at 4 and 24 h after i.v. administration of 111 MBq 123I-labeled antigranulocyte antibody Anti-NCA95. Scan results were interpreted without clinical information and were subsequently correlated with computed tomography. Prosthetic vascular graft infection was confirmed in 9 patients and excluded in 18 by surgical findings, bacteriology and/or clinical course. Scintigraphy revealed true-positive results in 16 of 40 and false-negative results in 1 of 40 examinations. True-negative results were found in 19 and 16, false-positive results in 4 and 7 examinations at 4 and 24 h p. i., resp. The sensitivity was calculated to be 94% for both early (4 h) and late (24 h) images whereas the specificity was 83% and 70%, resp. In all cases the application of the murine antibody was safe and no side effects or complications were noted. Limitations of this diagnostic procedure are accumulations of granulocytes in hematomas which may be observed in the non-complicated early course following reconstructive surgery.Es wurden 40 szintigraphische Untersuchungen bei 27 Patienten nach rekonstruktivem Gefäßersatz und klinischem Verdacht auf einen Gefäßprotheseninfekt durchgeführt. Ganzkörperaufnahmen wurden an der Gammakamera 4 und 24 h nach intravenöser Applikation von 111 MBq 123J-markiertem Antigranulozyten-Antikörper Anti-NCA95 durchgeführt. Die Resultate wurden ohne klinische Information ermittelt und anschließend mit den Ergebnissen der Computertomographie verglichen. Bei 9 von 27 Patienten konnte ein Gefäßprotheseninfekt durch chirurgisehe Intervention, Bakteriologie und/ oder klinischen Verlauf gesichert und bei 18 ausgeschlossen werden. Mittels Szintigraphie wurden richtig-positive Resultate bei 16 von 40 und falschnegative bei 1 von 40 Untersuchungen ermittelt. Richtig-negative Resultate fanden sich bei 19 und 16, falschpositive bei 4 und 7 Untersuchungen 4 bzw. 24 h p.i. Hieraus ermittelte sich eine Sensitivität von 94% für die Untersuchungen 4 und 24 h p. i. und eine Spezifität von 83 bzw. 70%. Die Applikation des murinen Antikörpers war sicher, Nebenwirkungen oder Komplikationen wurden nicht beobachtet. Während der Spätinfekt stets sicher zu diagnostizieren ist, kann es in der Frühphase nach allogenem Gefäßersatz selten zu einer unspezifischen Granulozytenanreicherung in nicht-infizierten perivaskulären Hämatomen kommen.